The fortunes of urban fullers in fourteenth-century England. Issue 260 (29th April 2020) - Pajic, Milan
Abstract: In the first half of the fourteenth century, for various reasons connected to the international market, urban clothmakers in England underwent a steady transition from producing light coarse cheap woollens, known as worsteds, towards producing heavily finished full woollens. One of the main beneficiaries of this shift were the urban fullers, as their economic position considerably improved relative to other textile trades. This article examines the development of their craft, looking at individual fullers in urban areas. It demonstrates how urban fullers rose to prominence throughout the fourteenth century.